Risk related to abuse of drugs in pregnant women - Santos, Rubia Mariana de Souza; Gavioli, Aroldo (Rev Rene, 2017)
Objective: to evaluate the risk related to drug use among pregnant women. Methods: this is a cross-sectional study, conducted with 209 pregnant women who answered the questionnaire for sociodemographic characterization and the Alcohol, Smoking, and Substance Involvement Screening Test. Descriptive and multivariate statistics were used.Results: there were 18.1% of the pregnant women with a moderate and high-risk level related to tobacco consumption, 27.2% with alcohol and 1.9% with marijuana. Levels of risk were statistically associated with less than eight years of non-white, Catholic education, living with a family of drug users, with a lower income than the sample mean, without children, living in a non-family household and aged between 14 and 24 years old. Conclusion: risk levels related to tobacco, alcohol, and marijuana consumption were high, being presented in vulnerable groups that should be the target of public policies for health promotion and prevention of drug use among pregnant women.